The influence of Human Resources Management Practices, and Government’s Role in the Organizational Performance of Small Businesses in Malaysia - Lazim, Yusra Yaseen; Noor Azlinna, Azizan (Integrated Publishing Association, 2013)
Performance appraisal (PA) is gradually becoming a part of a more strategic move towards integrating HR practices and organizational objectives and might now be seen as a general term covering a range of actions through which organizations seek to measure employees and increase their competence, improve performance and distribute rewards. The purpose of this paper is to investigate the relationship between performance appraisal and employee performance among employees of service and manufacturing sector organizations in India. Data was collected by standard questionnaire and random sampling from over 100 organizations both for service and manufacturing sectors. Correlation and regression analysis were used to explore the relationship between them. SPSS, Version 20 was used for analysis. Overall 52% and 32% of the variance in employee performance can be derived for by performance appraisal in the case of service sector organizations and manufacturing sector organizations respectively.